Transnationalization of Educational Aspirations: Evidence from China - Yasemin Nuhoglu Soysal; Héctor Cebolla Boado (Sociological Research Online, 2024)
The international migration of students has garnered a lot of attention from researchers due to its growing popularity and significance. However, the current state of research in this field is limited. On one hand, there is a scarcity of high-quality, large-scale data, and existing studies primarily focus on students who are already abroad. On the other hand, the field predominantly revolves around Bourdieusian-inspired arguments that narrowly view international education as a strategic investment by parents and a means of perpetuating social advantage. This article addresses these limitations by utilizing nationally representative survey data from China, the largest single source of international students globally. Our findings challenge the existing literature by revealing that parental aspirations to send their children abroad are more widespread across diverse social backgrounds than previously suggested. Furthermore, we observe that exposure to transnational environments amplifies aspirations for international education across various parental backgrounds and mitigates differences in aspirations based on parental education levels. We argue that these empirical patterns reflect the global standardization and diffusion of models and ideals of self, of which international education has increasingly become a part within the context of the transnationalization of higher education itself.
Keywords: 300; China; cultural capital and social reproduction; educational aspirations; global standardization of models and ideals of self; international education transnationalization of higher education